Zooplancton del Río Paraná Medio: variaciones temporales y distribucionales en el área de confluencia con el Río Paraguay - Bonetto, Argentino A.; Corrales de Jacobo, Marta A. (Ecosur, 2023)
The distribution, composition and numeric density of zooplankton communities at the first reach of Middle Paraná River were studied at the crosssection “Corrientes-Resistencia", about 30 km downstream its confluence with Paraguay River, by means of monthly samplings from April/76 to December/79. Samples were obtained one meter deph, fíltering 100 1 water with a 53 np mesh size sieve, at three stations: two located about 50 m from the margins (left at Corrientes and right at Chaco próvinces), and thé third at the centre of the section. Several Imnological parameters were recorded and water samples were taken to carry out current physical analysis at the laboratory. The numeric density of zooplankters and its specific composition, though very variable, resutted quite elevated (between 1 and 195 ind/l, with a total of 127 species), becoming both valúes more elevated towards the right margin. This river skle is very influenced by Paraguay River, wbile the left one, practically receive only Paranean waters. In spite of that, most zooplanktonic characteristic species in numerosity and frequence were generaüy similar in both margins.